1998
DOI: 10.1046/j.1365-2265.1998.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalences of Gsα, ras, p53 mutations and ret/PTC rearrangement in differentiated thyroid tumours in a Korean population

Abstract: ret/PTC rearrangement, Gs alpha, ras and p53 mutations are relatively rare in differentiated thyroid neoplasms from a Korean population, which may reflect genetic and environmental differences from patients in countries with high prevalences. P53 protein over-expression was noted in 13.3% of papillary carcinoma cases without p53 mutation and was not significantly related to MDM2 and Bcl-2 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 31 publications
9
51
0
Order By: Relevance
“…Meta-analysis of the data published worldwide over a greater than 10-year period (Table 3) demonstrates an average prevalence of 18% for Southern blotting (67/370 cases tested, range 0-33%), [26][27][28][29][30][31] 15% for direct visualization of the RT-PCR amplicons (47/309 cases tested, range 4-45%) 7,32-35 and 48% for hybridization of blotted RT-PCR products (153/314 cases tested, range 0-85%). 4,[21][22][23][36][37][38][39] Allowing for the fact that Southern blotting permits the identification of all RET/PTC variants while the cases analyzed by RT-PCR listed above only screened the tumors for RET/PTC1, -2 and -3, there is a good correspondence between the sensitivity of Southern blotting and of direct gel visualization of RT-PCR products, as also demonstrated by parallel analysis of the same samples with the two methods. 44 When RT-PCR is followed by blotting of the amplicons and hybridization with RET-specific probes the sensitivity increases dramatically, by at least 100-fold according to some investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis of the data published worldwide over a greater than 10-year period (Table 3) demonstrates an average prevalence of 18% for Southern blotting (67/370 cases tested, range 0-33%), [26][27][28][29][30][31] 15% for direct visualization of the RT-PCR amplicons (47/309 cases tested, range 4-45%) 7,32-35 and 48% for hybridization of blotted RT-PCR products (153/314 cases tested, range 0-85%). 4,[21][22][23][36][37][38][39] Allowing for the fact that Southern blotting permits the identification of all RET/PTC variants while the cases analyzed by RT-PCR listed above only screened the tumors for RET/PTC1, -2 and -3, there is a good correspondence between the sensitivity of Southern blotting and of direct gel visualization of RT-PCR products, as also demonstrated by parallel analysis of the same samples with the two methods. 44 When RT-PCR is followed by blotting of the amplicons and hybridization with RET-specific probes the sensitivity increases dramatically, by at least 100-fold according to some investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies regarding the immunohistochemical analysis of p53 expression have demonstrated that p53 overexpression may act as a significant and independent prognostic indicator for differentiated thyroid carcinomas (3,4,7,22,24). However, this association has provided controversial results (3,5,21,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In thyroid cancers, it was suggested that the presence of p53, as detected by immunohistochemistry, was associated with the occurrence of p53 gene mutations (5); however, the detection of p53 protein expression was also reported in differentiated papillary and follicular thyroid carcinomas regardless of the occurrence of p53 gene mutations; of note, the incidence rate of p53 protein overexpression in PTC was reported to be between 11 and 59% (4,(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In thyroid carcinomas, TP53 mutations are not different from those of cancers at other sites and have been described in exons 5-9, with 273 being the codon most often altered (42,67,69,70,71,72,73). No p53 expression or mutation has been found in normal thyroid or in benign lesions, including follicular adenoma, adenomatous goitre and chronic thyroiditis (72,73,74,75,76). For years it was repeated that more than 98% of DTC (PTC and FTC) had a normal TP53 gene (18,69,70,71,72,73,75,77), even when cases secondary to radiation exposure were included (78).…”
Section: Tp53 Mutationsmentioning
confidence: 99%